Analisis performa public relation digital PDIP dan PKS - Utomo, Yulius Wahyu Tri; Ahmad, Nyarwi (Universitas Bunda Mulia, 2023)
Managing public relations effectively is one of goal of public institutions, including Indonesian nationalist and Islamic political parties. This article is specified to examine the degree to which did PDIP dan PKS carry out political public relations activities and the ways they managed to do so as a political marketing strategy. To do so, we adopt Kiousis & Stromback’s (2013, 2014) political public relation theory and deploy descriptive qualitative method to anaylse the data derived from the existing literature, online news report and social media accounts of PDIP and PKS. The findings are as follows. PDIP and PKS have developed diverse types of political public relation (PR) activities. Each of these political parties strived to developed political PR activities. The ways they managed to do so are dissimilar. PDIP has prioritized to manage the media, issues and crisis managements. PKS has instead, preferred managing three following types of political PR activities, which are event management that is particularly directed to address the young electorates, campaign volunteer mobilization and also strategic digital communication and interactions, especially to the young voters targeted by this party much more. PDIP seems being less interested in establishing the abovementioned three political PR activities tactically